Green building technology and carbon footprint analysis - Xu, Ping Wei. (2011)
In Singapore, majority of the residents are housed in Housing Development Board (HDB) buildings. Most of these buildings are very old and they do not have the green technologies implemented. This would increase the energy consumptions and carbon emissions. The Singapore government‟s direction is to reduce carbon emission by year 2030. Therefore it is important to consider the possible areas of residential buildings where it could be more efficient in energy consumption. This study will make comparisons on different green technologies and their efficiencies. Building orientation, phase changing materials, window-to-wall ratio and green roof are the areas that will be discussed in this study. These technologies would be analysed in a simulation known as Virtual Environment (VE) software to calculate the annual energy consumption and carbon emission.